AI and Language: A Critical Discourse Analysis of Anima Anandkumar's AI TED Talk - Ahmad Vahry Lilam Putra; Fernanto, Hanny Wulandari; Yanwarita, Nabila; Suprayogi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study thoroughly investigates Anima Anandkumar's TED Talk, "AI that Connects the Digital and Physical World," to explore how the narrative of AI is built in the talk. This study employs Van Dijk's socio-cognitive method. The examination focuses on the analysis of discourse of the integration of AI into physical sciences. The study uses qualitative methods in gathering data based on Van Dijk’s three levels of framework, it includes; macrostructure, superstructure, and microstructure, it reveals how the idea exploration and linguistic features implemented by the speaker is carefully woven to emphasize the great implications of the speaker’s invention that serve as a bridge between AI and physical worlds. The results show how effective language is in spreading information about new developments in technology and the possible effects of artificial intelligence (AI) on different scientific domains. They also highlight the speaker's attempts to build trust and foster cooperation in the face of global issues. communities. This study contributes to the understanding of technological discourse and its influence on public and scientific communities for the general public.